A potential Rho GEF and Rac GAP for coupled Rac and Rho cycles during mesenchymal-to-epithelial-like transitions. (2nd January 2021) - Toret, Christopher P.; Le Bivic, Andre
ABSTRACT: The leading edge-to-cadherin contact transitions that occur during metazoan developmental processes and disease states require fine coordination of Rac and Rho pathways. Recently the elmo-mbc complex, a Rac GEF and RhoGAP19D, a Rho GAP were identified as key, conserved regulators that link Rac and Rho during these transitions. The corresponding Rho GEF and Rac GAP remain hidden amongst the large family of GEF and GAP proteins. Identification of these regulators is essential to understand GTPase coordination during these transitions. Here we find two candidates based on the mammalian literature and use RNAi to explore the fly ortholog effects on the dorsal closure epidermis. RhoGEF64C and RhoGAP92B are strong contenders to couple Rac and Rho during mesenchymal-to-epithelial-like transitions.